Focused molecular analysis of small cell lung cancer: feasibility in routine clinical practice. (December 2015) - Abdelraouf, Fatma; Sharp, Adam; Maurya, Manisha; Mair, Debbie; Wotherspoon, Andrew; Leary, Alex; Gonzalez de Castro, David; Bhosle, Jaishree; Nassef, Ayatallah; Gaafar, Taghrid; Popat, Sanjay; Yap, Timothy; et al.
Abstract Background There is an urgent need to identify molecular signatures in small cell lung cancer (SCLC) that may select patients who are likely to respond to molecularly targeted therapies. In this study, we investigate the feasibility of undertaking focused molecular analyses on routine diagnostic biopsies in patients with SCLC. Methods A series of histopathologically confirmed formalin-fixed, paraffin-embedded SCLC specimens were analysed for epidermal growth factor receptors (EGFR ), KRAS, NRAS and BRAF mutations, ALK gene rearrangements andMET amplification.EGFR andKRAS mutation testing was evaluated using real time polymerase chain reaction (RT-PCR cobas® ), BRAF andNRAS mutations using multiplex PCR and capillary electrophoresis-single strand conformation analysis, andALK andMET aberrations with fluorescent in situ hybridization. All genetic aberrations detected were validated independently. Results A total of 105 patients diagnosed with SCLC between July 1990 and September 2006 were included. 60 (57 %) patients had suitable tumour tissue for molecular testing. 25 patients were successfully evaluated for all six pre-defined molecular aberrations. Eleven patients failed all molecular analysis. No mutations inEGFR, KRAS andNRAS were detected, and noALK gene rearrangements orMET gene amplifications were identified. A V600E substitution inBRAF was detected in a Caucasian male smoker diagnosed with SCLC with squamoid and glandular features. Conclusion The paucity of patients with sufficient tumour tissue, quality of DNA extracted and low frequency of aberrations detected indicate that alternative molecular characterisation approaches are necessary, such as the use of circulating plasma DNA in patients with SCLC.